THE RELATIONSHIP BETWEEN LEARNING INTERESTS AND LEARNING HABITS AND THE RESULTS OF LEARNING MATHEMATICS IN GRADE VIII - Isna Choirunnisa; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Poor student learning outcomes are associated with many factors. The relationship between interest to learn and learning habits students is possibly related to learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship between interest to learn and learning habits student to Mathematics Learning Outcomes in Students Class VIII of State Junior High School (SMP Negeri) 13 Yogyakarta in Odd Semester in Academic Year of 2017/2018. The population in this research was the students of VIII of SMP Negeri 13 Yogyakarta in the academic year of 2017/2018, consisted of class VIII A, VIII B, VIII C, VIII D, totaling 130 students. Samples were taken from VIII D as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect the data of interest to learn and learn habits and test methods to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between interest to learn and learning habits student’s with mathematics learning outcomes in students class VIII of SMP Negeri 13 Yogyakarta in Odd Semester in Academic Year of 2017/2018. It is showed by Fcount  Ftable is  with 8 and  with , with  and RC ,  and